North Korea and Non-Aligned Movement (NAM) Lesson Learned and opportunities from North Korea Involvement in NAM - Triwibowo, Albert (Jurnal Ilmiah Hubungan Internasional, 2015)
Many experts still believe that engagement would be the answer towards the recent situation in Korean peninsula. Up to now, few contacts which have taken place can hardly be called as negotiations. Looking at the situation, a new player could be added into the negotiation process to solve North Koreaâs nuclear crisis. The new player should be free of interest, reliable, and has a strong connection with North Korea. It is already over 40 years since North Korea was accepted as full-fledged member and North Korea has gained immeasurably by joining Non-Aligned Movement (NAM). Thus NAM is probably one of the most promising exit strategies for North Korea nuclear crisis, the engagement that could provide coalition for punishment tomorrow. The movement could be an opportunity for North Korean nuclear problem, since it has long history with North Korea, freer from superpower interest, and provide a lot of benefits to North Korean regime.Â